Who the bishop knows - Chapman, Vannetta (Chapman, Vannetta. Amish Bishop mysteries, 2018)
"Every year, residents of the small Amish community in Monte Vista, Colorado, look forward to the Ski Hi Stampede, the state's oldest professional rodeo. The rodeo is always good, clean entertainment for the hardworking farmers of the San Luis Valley. But this year, the Stampede turns deadly for one Amish man. Did rodeo fans see an unfortunate accident? Or something more sinister? Amish bishop Henry Lapp is known far and wide for his uncanny ability to draw and remember the smallest details of anything he's seen, skills that have served him well in past investigations. He was at the rodeo that day. The problem? He didn't see Jason Scott's death. With a murderer on the loose and members of his community being threatened, Henry must act fast. But can he solve a crime he didn't see? This time around, Henry will have to rely on his keen sense of human character and observation, skills he's honed in his role as bishop, if he hopes to crack the case. What the Bishop Knows is a story of accepting our talents, putting one another first, and trusting that God will care for His children"--